Bias and discrimination in intra-household food allocation: case study of a rural labour population in northeast Brazil - Hansford, F (2010)
My thesis examines food allocation and nutritional outcomes in a sample of 152 individuals in thirty-two households of sugarcane workers in the municipality of Gameleira, Northeast Brazil. Anthropometric data show that undernutrition and overnutrition coexist in the study population, and often within households – a consequence of the changes in diet and physical activity linked to the nutrition transition. Food allocation was examined using an indicator of the frequency of consumption of high status foods - non-staple foods which are considered more desirable than staples because they add variety and taste to an otherwise monotonous diet. I created an intra-household index of food allocation in order to observe each individual's consumption in relation to the average in his or her household at two seasonal points of the year. The sample was split into two groups, a group of more affluent households in which high status foods were eaten on the harvest and non-harvest dietary recalls, and a group of less affluent households in which no-one ate high status foods on the non-harvest recall. I found gender biases in the allocation of food in favour of men relative to women, and girls relative to boys, in the higher income group, but no gender biases in the group of less affluent households. In relation to age, I found biases in favour of children relative to adults in less affluent households, but not during seasonal shortage in the higher income households. The biases were greater in households with higher incomes, but lower in households in which women controlled some household income relative to households in which men controlled all income. I considered whether discriminatory behaviour underpins these biases, based largely on periods of observation in a sub-sample of six households, and concluded that food distribution operates as a powerful medium for the expression of differential status among men and women, but not among boys and girls, who have equal status in this population.